The Morphology and Syntax of Tagalog Nouns and Adjectives - Paz, Consuelo J. (The Archive; Vol 11 (1996): Publication Eleven: Three Studies on Philippine Morphology, 2025)
This paper is an attempt to describe, classify, and analyze the nouns and adjectives of Tagalog. 1 Chapters II and III present the morphology of the nouns and adjectives respectively. Chapter IV describes the positions and functions of the nouns and adjectives in different syntactic constructions. Chapter V summarizes the morphophonemic changes in the nouns and adjectives.